An Integrated Approach to Characterize Temporal–Spatial Variations in PM2.5 Concentrations at the Ground Level and Its Implication on Health Impact Assessments - Ho, Ming-Shing; Lin, Ming-Yeng; Wang, Jung-Der; Young, Li-Hao; Hsu, Hui-Tsung; Hwang, Bing-Fang; Tsai, Perng-Jy (Frontiers in Environmental Science, 2022)
Though PM2.5 concentrations measured by the governmental air quality monitoring station (AQMS) have been widely used for conducting exposure assessment, it might be not able to reflect residents’ exposures, especially for those associated to ground emissions. The present study was conducted in a city area for one year. A mobile monitoring station (MMS) was established to measure PM2.5 concentrations of the ground level. A significant linear relationship (R2 = 0.53) was found between MMS measured concentrations and the corresponding concentrations obtained from AQMS (15 m above the ground level), and the former was ~1.11 times (95% CI: 1.08-1.15) in magnitude higher than that of the latter. To characterize the spatial variation of the area, the MMS measured values were further classified in to three different regions. A consistent trend was found in the present study for all collected data as: industry region≒urban region>harbor region. The above results clearly indicate that residents’ ambient PM2.5 exposures do exist spatial differences. A seven-year AQMS measured concentrations (i.e., AQMS7-yr) were used to establish the long-term PM2.5 concentrations at the ground level (i.e., MMS7-yr) of the three different regions using the linear regression equations obtained from MMS and AQMS. Health impact functions and local health data were used to quantify the PM2.5-attributable health burden for both AQMS7-yr and MMS7-yr, respectively. Results show that the former is ~10.4% in magnitude lower than that of the latter in the estimated lung cancer death attributed fraction (AF). In particularly, the decrease of unit PM2.5 (μg/m3) would lead to a 0.75% and 0.71% decrease in the estimated AF of the lung cancer death for AQMS7-yr and MMS7-yr, respectively. As a result, directly using AQMS7-yr would lead to an underestimation of ~1,000 lung cancer deaths annually in Taiwan as in comparison with those using MMS7-yr. The above results clearly indicate the importance of characterizing the ground level exposures for assessing the health impact of residents, and the methodology developed by the present study would be helpful for solving the above problem.